A compact NiTi elastocaloric air cooler with low force bending actuation. (October 2022) - Li, Xueshi; Cheng, Siyuan; Sun, Qingping
Graphical abstract: Highlights: Decreasing the specific driving force of NiTi sheet to 5.64 N·g − 1 by bending. Elastocaloric air cooler with single-row bent NiTi sheets and an air duct is built. Cooler outputs an air flow of 5.5 K lower than room temperature. Concept of lift air duct design for the elastocaloric air cooler. Great potential to develop a 1 kW elastocaloric air cooler. Abstract: Elastocaloric cooling has emerged as a promising alternative to traditional vapor-compression refrigeration, and miniaturization is essential for commercialization of this cooling technology. Here, a compact NiTi elastocaloric air cooler with low force bending actuation is presented. The phase transformation of bent NiTi sheets (with a maximum strain of 7.20% on the surface of tension side) is induced at a specific driving force of 5.64 N·g −1, which is at least two orders of magnitude lower than those of tensive and compressive modes. The cooler with single-row bent NiTi sheets and air duct is studied, achieving an output air flow of 5.5 K temperature reduction in the cooling cycle and a maximum specific cooling power of 0.137 W·g −1 in experiments. The cooler with multi-row NiTi sheets produces a maximum cooling power of 11.5 W at the current stage. These results show a development potential for the compact and miniature elastocaloric cooling device.